Psychological Skills of Highly Qualified Football Players, Determining the Effectiveness of their Playing Activities - Irina Simonenkova; Vladimir Sopov, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
The paper presents research findings of the psychological skills of highly qualified football players. These skills are essential for effective football players. Based on the analysis of the results, obtained by using the author’s methodology, method of expert assessment and statistical methods, the psychological skills that are related to the game efficiency of the players have been established.